The effect of silver nanoparticles on the limitation of ethylene gas and hydrolytic enzymatic activity in micropropagation of rose (Rosa hybrida L. 'Baby love') - Ngan, Ha Thi My; Tung, Hoang Thanh; Nghiep, Ngo Dai; Le, Bui Van; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2020)
Micropropagation of rose (Rosa hybrida L. ‘Baby Love’) often encounter some abnormal phenomena such as yellow and abscission leaf, hyperhydricity, etc. These phenomena effect on the quality of shoots cultured in vitro as well as the survival rate of plantlets after transferred to greenhouse. This is due to the accumulation of ethylene in culture vessel, which leads to an increase in enzyme activity of cellulase and pectinase resulted in disrupting the cell wall binding and inducing organ abscission. In this study, the effect of silver nanoparticles (AgNPs) to overcome these abnormal phenomena as well as its effect on the growth and development of shoots and plantlets in rose cultured in vitro were evaluated. The results showed that after 6 weeks of shoot culture, the medium supplemented with 2 ppm AgNPs was the most suitable for in vitro shoot multiplication with the highest number of shoots/explant (6.67 shoots), shoot height (3.06 cm), fresh weight (451.00 mg), dry weight (58.33 mg), SPAD (32.28) and dry mass ratio(12.33%). Adding 3 ppm AgNPs into in vitro rooting medium may improve the growth and develop involve in plant height (3.06 cm), number of leaves (6.33), leaf length (1.50 cm), leaf width (1.50 cm), fresh weight (137.67 mg), dry weight (13.00 mg), number of roots (4.33), SPAD (39.37), dry mass ratio (9.40%) of rose plantlet after 4 weeks of culture. After treatment with AgNPs, the abnormal phenomena including ethylene gas accumulation (0.30 ppm), cellulase enzyme activity (0.14 UI/mL) and pectinase enzyme activity (0.40 UI/mL) was reduced compare with the other treatments and the control. In addition, the high survival rate (93.33%) of plantlets was also observed after 4 weeks transferred to greenhouse. On the other hand, the treatment with 5 ppm AgNPs also induced early rose in vitro flowering; however, when using AgNPs at high concentrations (7 ppm) inhibited growth, development, toxicity and even death of explants.